Less Contact Society Melalui Pemanfaatan Website Masjid Al-Ihsan Komplek Aru Indah Kota Padang - Ahmad Kamal; Renita Astri; faradika faradika (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
The process of implementing the financial management of the al Ihsan mosque is still done manually and there is still frequent physical contact between the mosque administrators and between the administrators and the congregation. All financial reporting is still recorded on the blackboard which is displayed on one of the inner walls of the mosque. Every community who wants to donate their funds must report and meet directly with the mosque management. Likewise, if the public wants to know the current state of the mosque's cash. So that there is still direct physical contact between people. For this reason, the Dharma Andalas University (UNIDHA) Information System lecturer team tries to help through the use of information technology in the form of a mosque website which functions to provide more complete information with a wider reach to the general public about the al-Ihsan mosque but still by carrying out and prioritizing the concept of Less. Contact Society in order to maintain the safety and health of the community in the al Ihsan mosque environment.